Effect of service quality PT. Cross Marga Sedaya on consumer satisfaction in use e-toll card on Cipali toll road - Endah Budiastuti; Nindiya Agustin (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2021)
This research is motivated by the finding when the toll gates on the Cipali toll road do not provide transaction service satisfaction and services that are not in accordance with customer expectations such as the availability of substations at the gate which in reality cannot meet the surge in customers, especially during working hours and on holidays. In addition, the availability of ramps is also not proportional to the number of vehicles exiting the Cipali toll gate. This shows that there are problems regarding transaction services which have implications for the low transaction speed of toll road customers. To test these variables, researchers used hypothesis testing using simple regression and quantitative methods using correlational techniques. The data analysis technique uses a simple regression technique. The results showed that the influence of PT.Lintas Marga Sedaya's service quality on consumer satisfaction in using the E-Toll Card on the Cipali toll road was in the very strong category. This is based on the value of rcount = 0.937 which is in the correlation interval 0.800–1,000 with a very strong category. In order to determine the significance level at = 0.05 (5%) the value of tcount = 26,216 and ttable = 1.66105. Thus, tcount > ttable, which means that there is a significant effect between variable X on variable Y, where the contribution of service quality to satisfaction is large. consumers by 87.9% and the remaining 12.1% is influenced by other factors not examined in this study.